The Influence of Public Asset Management Effectiveness, Digitalization and Transparency on Fiscal Sustainability: An International Literature Review - Lubis, Nurliza; Lubis, Nasrul Kahfi; Syardiansah, Syardiansah; Girma, Abebe Gule (Journal of Management and Business Innovations, 2024)
This study aims to analyze the influence of public asset management effectiveness, digitalization, and fiscal transparency on fiscal sustainability through an international literature review. Employing a Systematic Literature Review (SLR) and bibliometric analysis using VOSviewer and Harzing’s Publish or Perish software, this research examines 56 publications from 2015 to 2025. The findings reveal that each variable has a significant positive impact on fiscal sustainability. More importantly, the integration of all three creates synergistic effects that enhance fiscal efficiency, accountability, and predictive budgeting capacity. Country cases such as South Korea, Estonia, and Indonesia illustrate that the success of reform depends on institutional readiness, digital system interoperability, and strong political commitment to transparency. This study contributes to strengthening tech-enabled fiscal governance and opens new pathways for sustainable fiscal policy research, particularly in developing countries.Keywords: Digitalization, Fiscal Sustainability, Fiscal Transparency, Public Asset Management, Public Financial Governance.